SPK Seleksi Calon Karyawan PT Jasa Raharja Menggunakan Metode Kombinasi ARAS dan Weighted Product - Sri Rahmayani (STIKes Ibnu Sina Ajibarang, 2025)
PT Jasa Raharja is one of the state-owned enterprises (BUMN) operating in the insurance services sector. The employee selection process often involves subjectivity and a lack of consistent evaluation standards, making it less effective. With the implementation of a Decision Support System (DSS), this assessment process can be carried out meticulously, considering various criteria that influence the final decision. The outcome of this ranking process will determine the most suitable candidate for acceptance. To achieve accurate results, the ARAS and Weighted Product comparison methods are applied. The data used are derived from the company's criteria. The criteria utilized in this study include interviews, psychometric tests, work experience, age, and education. The results of this study produced different rankings: Irfan, according to the ARAS method, has a preference weight of (0.8912), while in the WP method, he has a preference weight of (0.1229).